Georg Hermann Stoltz Ein Kaufmann zwischen Hamburg und Brasilien - Schröder, Hans Joachim (Mäzene für Wissenschaft, 2018)
Georg Hermann Stoltz was distinguished by his vision for economic development and his determined pursuit of a wide range of activities, as well as by his good knowledge of human nature, leadership, sales talent, and reliability. With this volume, the first biography of Georg Hermann Stoltz (1845-1939) is available. It provides valuable insights into the life of a man who, as a successful merchant and company founder in Brazil and Hamburg, has rendered outstanding services to relations between South America and Europe. The biography was written by Hans Joachim Schröder; it is the 21st volume in the series "Mäzene für Wissenschaft" published by the Hamburg Scientific Foundation. in many respects, Georg Hermann Stoltz is a typical representative of the group of Hamburg patrons who established the Hamburgische Wissenschaftliche Stiftung with their donations in 1907, thus enabling the foundation of the Hamburg University twelve years later: Like most others, he worked as an overseas merchant. Like some of the other members of the group, he built up extensive trade between South America, especially between Brazil and Hamburg. In the course of his long life he thus became a pioneer of German-Brazilian relations. His wealth allowed him to establish a generous residence in Wentorf near Hamburg and a foundation in Lüneburg, where he attended school at the Johanneum. In all this he became the ancestor of a large family that is still alive today.